Engineering Escherichia coli for diagnosis and management of hyperuricemia - Gencer, Gozde; Mancuso, Christopher; Chua, Koon Jiew; Ling, Hua; Costello, Cait M.; Chang, Matthew Wook; March, John C. (Frontiers in Bioengineering and Biotechnology, 2023)
Uric acid disequilibrium is implicated in chronic hyperuricemia-related diseases. Long-term monitoring and lowering of serum uric acid levels may be crucial for diagnosis and effective management of these conditions. However, current strategies are not sufficient for accurate diagnosis and successful long-term management of hyperuricemia. Moreover, drug-based therapeutics can cause side effects in patients. The intestinal tract plays an important role in maintaining healthy serum acid levels. Hence, we investigated the engineered human commensal Escherichia coli as a novel method for diagnosis and long-term management of hyperuricemia. To monitor changes in uric acid concentration in the intestinal lumen, we developed a bioreporter using the uric acid responsive synthetic promoter, pucpro, and uric acid binding Bacillus subtilis PucR protein. Results demonstrated that the bioreporter module in commensal E. coli can detect changes in uric acid concentration in a dose-dependent manner. To eliminate the excess uric acid, we designed a uric acid degradation module, which overexpresses an E. coli uric acid transporter and a B. subtilis urate oxidase. Strains engineered with this module degraded all the uric acid (250 µM) found in the environment in 24 h, which is significantly lower (P<0.001) compared to wild type E. coli. Finally, we designed an in vitro model using human intestinal cell line, Caco-2, which provided a versatile tool to study the uric acid transport and degradation in an environment mimicking the human intestinal tract. Results showed that engineered commensal E. coli reduced (P<0.01) the apical uric acid concentration by 40.35% compared to wild type E. coli. This study shows that reprogramming E. coli holds promise as a valid alternative synthetic biology therapy to monitor and maintain healthy serum uric acid levels.